Edukasi Etika Berkomunikasi Di Media Sosial Dan Literasi Hukum Siber Bagi Siswa SMPN 5 Subang Melalui Diskusi Interaktif - Wulandari Wahyudin; Sopianna Agung Septina Pardede; Putri Samrotul Fuadah; Moch. Fauzi Abdurrohim; Desti Kusmayanti; Esti Andarini; Yudisa Diaz Lutfi Sandi (Pusmedia Group Indonesia, 2026)
The use of social media among junior high school youth is often not accompanied by an understanding of communication ethics and cyber law awareness, which potentially triggers cyberbullying, hate speech, and the spread of hoaxes. This community service activity aims to increase students' interest, motivation, and understanding of digital language politeness and cyber law literacy at SMPN 5 Subang through a dialogic interactive discussion approach. The service method was implemented using David Kolb's Experiential Learning approach, which includes four systemic stages of experience-based learning cycles: concrete experience, reflective observation, abstract conceptualization, and active experimentation. In the action stage, the program was realized through socialization and simulation of contextual digital problem-solving that is close to teenagers' daily lives. The results of this activity showed a significant increase in students' emotional involvement and active participation. Students were able to practice sharp critical awareness, explore netizen legal boundaries through UU ITE case studies, and collaborate to formulate a collective